EFFORTS TO PREVENT STUNTING IN FAMILIES WITH TODDLERS BASED ON THE PLANNED BEHAVIOR THEORY APPROACH IN LAMPULO VILLAGE, BANDA ACEH CITY - Desreza, Nanda; Mulfianda, Riyan; Nurmalia (Transpublika Publisher, 2022)
Malnutrition in young individuals can have severe consequences, including complex issues such as short stature and stunting. Stunting during early childhood can negatively impact intelligence quotient (IQ), psychomotor development, motor skills, and neurosensory integration. Therefore, the role of parents in preventing stunting is crucial. The aim of this research is to investigate strategies for preventing stunting among families with newborns using the Planned Behavior Theory approach in Lampulo Village, Banda Aceh City, in 2019. This research is a descriptive correlation study with a cross-sectional approach, conducted from August 7th to 31st, 2019. The study's population consisted of all mothers at risk of stunting in Lampulo Village, Banda Aceh City, with a sample size of 74 people selected through proportional sampling. The study's results indicated that there was a significant influence of behavioral beliefs (p=0.011), normative beliefs (p=0.021), and control beliefs (p=0.020) on stunting prevention in families with young children. It is hoped that this research can provide valuable insights to healthcare providers and community health centers (posyandu) in delivering information on stunting prevention.